Outcome of Surfactant Replacement Therapy in Preterm Babies with Hyaline Membrane Disease at Neonatal Intensive Care Unit of a Tertiary Hospital - Manandhar, Sunil Raja (Birat Journal of Health Sciences, 2019)
Introduction: Hyaline membrane disease (HMD) is an acute lung disease of preterm babies caused by surfactant insufficiency. Decreased surfactant results in insufficient surface tension in the alveolus during expiration leading to alveolar collapse, atelectasis, impaired gas exchange, severe hypoxia and acidosis, leading to respiratory failure. Surfactant replacement therapy (SRT) is now accepted as the standard treatment of preterm babies with HMD. Objective: The objective of this study was to analyze the outcome of surfactant replacement therapy in preterm babies with hyaline membrane disease. Methodology: This is a prospective observational study conducted at 10 bedded neonatal unit of Pediatrics Department, Kathmandu Medical College Teaching Hospital, Sinamangal. Study duration was of one year period (15 May 2017 – 14 May 2018). Preterm babies from 26 wks–35 wks of gestation with Hyaline Membrane Disease were included in this study whereas babies with lethal congenital malformations eg: Meningomyelocele, Anencephaly, Gastrochisis, Diaphragmatic Hernia were excluded. All preterm babies who had clinical and radiological features of HMD were considered for Surfactant Replacement Therapy (SRT). The surfactant (Survanta; Abboti Laboratories, USA; Dose: 4 ml/kg) was administered intra-tracheally according to standard procedures in four divided aliquot applying INSURE (intubation, surfactant administration and extubation to Bubble CPAP) Technique. Ethical clearance was received from Institutional Review Committee (IRC) of Kathmandu Medical College and Statistical analysis was done with SPSS 19 version with frequency and cross tabulation. Results: In this study of 30 preterm babies with HMD received SRT, 47% (14) were male and 53% (16) were female. The mean birth weight of preterm babies with HMD was 1372.17 ± 395 gms and mean gestational age was 30.1±2.6 weeks. Among 30 preterm babies with HMD receiving SRT, 73.3% (22 babies) discharged from the hospital and 6.3% (8 babies) expired. Among eight expired babies, five died due to pulmonary hemorrhage and three died due to septicemia with DIC. Maximum survival was seen in the gestational age of 30-35 wks and birth weight 1200-2100gms. Conclusion: The use of SRT has improved the survival outcome and decreased the associated morbidities in babies with HMD. The maximum impact of survival was seen among the preterm babies of 30- 35 weeks with birth weight of 1200 -2100 grams.